A randomized comparison between intravenous and perineural dexamethasone for ultrasound-guided axillary block - Julian Aliste (2018)
© 2016, Canadian Anesthesiologists' Society. Background: This randomized double-blinded trial compared the effect of intravenous and perineural dexamethasone (8 mg) on the duration of motor block for ultrasound (US)-guided axillary brachial plexus block (AXB). Methods: Patients undergoing upper limb surgery with US-guided AXB were randomly allocated to receive preservative-free dexamethasone (8 mg) via intravenous (n = 75) or perineural (n = 75) administration. The local anesthetic agent, 1% lidocaine −0.25% bupivacaine (30 mL) with epinephrine 5 µg·mL −1 , was identical in all subjects. Operators and patients were blinded to the nature of the intravenous and perineural injectate. A blinded observer assessed the block success rate (i.e., a minimal sensorimotor composite score of 14 out of 16 points at 30 min), block onset time, as well as the presence of surgical anesthesia. Postoperatively, the blinded observer contacted all patients with successful blocks to record the duration of motor block (primary outcome), sensory block, and postoperative analgesia. Results: No intergroup differences were observed in terms of success rate, surgical anesthesia, and block onset time. Compared to intravenous administration, perineural dexamethasone provided longer mean (SD) durations for motor block [17.5 (4.6) hr vs 12.8 (4.5) hr; mean difference, 4.6 hr; 95% confidence interval [CI], −6.21 to −3.08; P  <  0.001], sensory block [17.7 (5.1) hr vs 13.7 (5.0) hr; mean difference, 4.0 hr; 95% CI, −5.77 to −2.27; P  <  0.001], and postoperative analgesia [21.1 (4.6) hr vs 17.1 (4.6) hr; mean difference, 4.0 hr; 95% CI, −5.70 to −2.30; P  <  0.001]. Conclusion: Compared to intravenous dosing, perineural dexamethasone (8 mg) results in longer durations of sensorimotor block and postoperative analgesia for ultrasound-guided axillary block. This trial was registered at www.clinicaltrials.gov number, NCT02629835.